Lower bounds for the module of determinants of block diagonally matrices - Zarnan, Jumah; Petkov, Milko (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1994)
In the present paper a lower bounds for the block matrices with strongly dominant diagonal and one-sided dominant diagonal have been obtained.